Echocardiogram changes following parathyroidectomy for primary hyperparathyroidism: A systematic review and meta-analysis. Issue 43 (October 2017) - Best, Corliss A.E.; Krishnan, Rohin; Malvankar-Mehta, Monali S.; MacNeil, S. Danielle
Abstract : Abstract: The aim of the study is to systematically review the evidence on post parathyroidectomy (PTX) changes as measured by echocardiogram (ECHO) in patients with primary hyperparathyroidism (PHPT). PHPT may increase risk of cardiovascular morbidity/mortality. Conclusions of studies assessing ECHO changes, pre versus post PTX, are inconsistent. A systematic literature search was conducted to locate published and unpublished studies. Randomized control trials, nonrandomized control trials, and observational studies were included. Variables were reported as means and standard deviations. An inverse variance statistical method, with random-effects analysis model, was applied to continuous data. The effect measure was standardized mean difference, confidence interval of 95%. Primary outcome measure was left ventricular ejection fraction (LVEF). Secondary outcome measures were left ventricular mass index (LVMI), peak early over peak late diastolic velocity ratio (E/A ratio), isovolumetric relaxation time (IVRT), intraventricular septal thickness (IVST), and posterior wall thickness (PWT). Fourteen studies were included. Follow-up time ranged 3 to 67 months. No significant differences ( P > .05) in primary outcome measure LVEF (SMD = −0.03, CI = −0.24, 0.19), or secondary outcome measures E/A Ratio (SMD = −0.05, CI = −0.24, 0.14), IVST (SMD = 0, CI = 0.31, 0.32), PWT (SMD = 0.01, CI = −0.38, 0.39), LVMI (SMD = −0.18, CI = −0.74, 0.38), and IVRT (SMD = −0.84, CI = −1.83, 0.14) were observed. There was no significant difference in LVEF pre to post PTX. Due to heterogeneity of current literature, we were unable to determine if other outcome measures of cardiac function are affected after PTX in patients with PHPT. We recommend a randomized control trial be conducted to make concrete conclusions.